Effects of Dietary Supplementations of Synbiotics on Growth Performance, Carcass Characteristics and Nutrient Digestibility of Broiler Chicken - Nisar,H (2021)
ABSTRACT The study aimed to explore the effect of dietary supplementation of synbiotics on growth performance, carcass characteristics and nutrient digestibility in broiler chicken. For this purpose, three hundred 1-day-old Cobb-500 broiler chicks were purchased from the hatchery and randomly distributed into five dietary treatment groups. Each treatment had six replicates, each containing 10 chicks. The experimental diets were supplemented with 0, 700, 1200, 1700 or 2200 g/ton of feed synbiotics and respectively designated as A, B, C, D and E, with A being the control diet. Feed intake, weight gain and feed conversion ratio data were recorded on a weekly basis. At the research trial’s end, two birds from each pen were randomly selected and slaughtered to get data on carcass characteristics. Results showed that group C’s feed intake was reduced (p<0.05) when compared to control. Body weight was similar (p>0.05) among all treatments. However, feed conversion ratio was significantly improved (p<0.05) in group C as compared to other dietary treatments. Nutrient digestibility was improved (p<0.05) in group B and C, as compared to control. Carcass characteristics were not significantly affected and remained the same across all treatments. However, liver weight decreased in birds fed diet C. Meat quality and antibody titer were not affected in any of the dietary treatments. It is concluded that synbiotics can be safely used up to 1200 g/ton of feed, improving bird performance without harmful effects on bird health.